Intelligent Robotics and Applications First International Conference, ICIRA 2008 Wuhan, China, October 15-17, 2008 Proceedings, Part I - Xiong, Caihua.; Xiong, Caihua.; Huang, Yongan.; Huang, Yongan.; Xiong, Youlun.; Xiong, Youlun. (Lecture Notes in Artificial Intelligence, 2008)
These two volumes constitute the refereed proceedings of the First International Conference on Intelligent Robotics and Applications, ICIRA 2008, held in Wuhan, China, in October 2008. The 265 revised full papers presented were thoroughly reviewed and selected from 552 submissions; they are devoted but not limited to robot motion planning and manipulation; robot control; cognitive robotics; rehabilitation robotics; health care and artificial limb; robot learning; robot vision; human-machine interaction & coordination; mobile robotics; micro/nano mechanical systems; manufacturing automation; multi-axis surface machining; realworld applications.